TINGKAT PENGUNGKAPAN DAN PENGGUNAAN DERIVATIF KEUANGAN DALAM AKTIVITAS PENGHINDARAN PAJAK - Oktavia, Oktavia; Martani, Dwi (UI Scholars Hub, 2013)
The purpose of this study is to investigate whether, in a case study of Indonesia, financial derivatives are used as a means of tax avoidance as literature shows that derivative users incline to avoid tax. Two samples treatment are conducted in examining the problem. Initially, using the sample all derivative users, this study does not find that derivative users are significantly related to tax avoidance. However, when the sample is separated into two groups based on the level of disclosure on financial derivatives, the results show otherwise. Firms with low level of disclosure on financial derivatives is more tax aggressive compared to those with high level of disclosure. These findings are shown by their lower ETRs (Effective Tax Rate) compared to other firms. Moreover, this study also examines the relationship between the use of financial derivatives with the level of tax avoidance. The results indicate that the use of financial derivatives is positively related to the level of tax avoidance. Results of this study are expected to have positive contribution on the development of tax policy in Indonesia, particularly for the tax on derivatives.